Association between environmental air pollution and rheumatoid arthritis flares. (20th January 2021) - Adami, Giovanni; Viapiana, Ombretta; Rossini, Maurizio; Orsolini, Giovanni; Bertoldo, Eugenia; Giollo, Alessandro; Gatti, Davide; Fassio, Angelo
Abstract: Objectives: Environmental air pollution has been linked to the pathogenesis of RA. Nevertheless, evidence linking higher concentrations of air pollutants with the risk of RA reactivations is missing. The objective of the present study was to determine the association between RA flares and air pollution. Methods: We collected longitudinal data of patients affected by RA and of the daily concentration of air pollutants in the Verona area. We designed a case-crossover study. We compared the exposure to pollutants in the 30‐day and 60-day periods preceding an arthritic flare referent to the 30‐day and 60-day preceding a low-disease activity visit. Results: The study included 888 patients with RA with 3396 follow-up visits; 13 636 daily air pollution records were retrieved. We found an exposure–response relationship between the concentration of air pollutants and the risk of having abnormal CRP levels. Patients exposed to greater concentrations of air pollutants were at higher risk of having CRP levels ≥5 mg/l. Concentrations of CO, NO, NO2, NOx, PM10, PM2.5 and O3 were higher in the 60-day period preceding a flare. Conclusions: We found a striking association between air pollution and RA disease severity and reactivations in a cohort of patients followed over a 5-year period. The exposure to high levels of air pollutants was associated with increased CRP levels and a higher risk of experiencing a flare of arthritis. This excessive risk was evident at very low levels of exposure.